Blind vs. video-laryngoscope-guided laryngeal mask insertion: A prospective randomized comparison of oropharyngeal leak pressure and fiberoptic grading - SARAÇOĞLU, AYTEN (My University, 2022)
Purpose Laryngeal Mask Airway (LMA) insertion may not always be smooth without complications. Controversial results of several studies evaluating ideal insertion conditions have been published. This study compared the oropharyngeal leak pressure values and fiberoptic grading scores between blind and video-laryngoscope-guided LMA insertion. Methods Patients were randomly assigned into blind insertion (n = 50) and video-laryngoscope guided insertion (n = 50) groups. The oropharyngeal leak pressure, peak airway pressure, fiberoptic grading score, first attempt success rate, hemodynamic parameters, and complications were recorded. Results All laryngeal mask airways were successfully inserted in both groups at the first attempt. The fiberoptic staging scores were: grade 1 in 8.2% of patients, grade 2 in 24.4% of patients, grade 3 in 44.8% of patients, grade 4 in 22.4% of patients in the control group. On the other hand, grade 1 in 2.2% of patients, grade 2 in 28.6% of patients, grade 3 in 51% of patients, grade 4 in 8.2% of patients in the VL group (p = 0.260). The peak airway pressure and LMA insertion time were similar between groups. However, the oropharyngeal leak pressure before extubation was significantly higher in the video-laryngoscope-guided insertion than blind insertion (36.29 +/- 7.09 vs. 33.79 +/- 8.84 cmH2O respectively, p = 0.04). Conclusions The findings of our study suggest that the video-laryngoscope-guided LMA-Classic insertion with a standard blade technique may be a helpful alternative to blind insertion.
Keywords: Tıp; Sağlık Bilimleri; Cerrahi Tıp Bilimleri; Anesteziyoloji; Medicine; Health Sciences; Surgery Medicine Sciences; Anesthesiology; ANESTEZİYOLOJİ; Klinik Tıp; Klinik Tıp (MED); ANESTHESIOLOGY; CLINICAL MEDICINE; Clinical Medicine (MED); Anesteziyoloji ve Ağrı Tıbbı; Anesthesiology and Pain Medicine; Blind insertion; Laryngeal mask airway; Video-laryngoscope; AIRWAY DEVICES; SUPRAGLOTTIC AIRWAY; PLACEMENT; INTUBATION; POSITION; SUPREME; PROSEAL